Correlation Among Positive PCR COVID-19 Patient’s Clinical Outcome and Balanced Nutrition (Medical Forum Monthly, 2023)
Objective: To study the nutritional status and disease outcome association in patients suffering from COVID 19.Study Design: Cross sectional (Descriptive) study.Place and Duration of Study: It was 6 months study after approval from research and ethical committee Women Medical and Dental College Abbottabad done on COVID-19 patients quarantined at different places in district Mansehra to check the COVID-19 being impacted by nutritional status on COVID-19 outcome in PCR positive patients. This study was conducted at the King Abdullah Hospital, Manshera from June 2021 to December 2021 (six months).Materials and Methods: Cross sectional (descriptive) study was done on PCR positive sufferers quarantined at home and at different quarantine centers with complete SOPs and were assessed by anthropometric measurement and dietary assessment by FFQ and 24 hours dietary recall methods. A pre designed questionnaire was used for demographic variables. latest SPSS version was applied to rationalize statistical results.Results: Results show the duration of the quarantine period and mean age of the patients 31 years and 7-14 days respectively, while standard deviation for age of the patients and quarantine period were 15.02, and 2.10 respectively. Std. Error of Skewness values for age of the patients and quarantine period were 0.17, and 0.79 respectively and 2-tailed significance show strong correlationDuration of the hospital stay was recorded longer in 7 patients while shorter in 193 patients with 188 cases having quarantined at home and 12 at quarantine centers. Spearman’s rho is significant for hospital admission history, fever and outcome of the disease while negative with heights and weights of the patients. Vitamin C & D serum levels were different in both males and females, while serum Ferritin levels, serum calcium and serum zinc levels showed strong correlation with immunity enhancement in favorable outcome of the COVID-19 patients and NRS score, duration of Quarantine period.Conclusion: There is positive correlation between good nutritional status and decrease in quarantine period for COVID-19.